Tuturan Laku Among dalam wacana kelas - Suwignyo, Heri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This study aims to describe and explain laku among utterances in classroom discourse. Laku among speech acts are a natural phenomenon of language use in social and cultural contexts. To explain this phenomenon, ethnographic research was employed based on the structure of classroom communication. The results of the study show three findings regarding the use of laku among utterances in the classroom: ing ngarsa, ing madya, and tut wuri handayani, which occur in the initial, middle, and final speech acts of classroom discourse.